1978
DOI: 10.1210/endo-103-3-871
|View full text |Cite
|
Sign up to set email alerts
|

The Irreversible Inactivation of Thyroid Peroxidase by Methylmercaptoimidazole, Thiouracil, and Propylthiouracil in Vitro and Its Relationship to in Vivo Findings*

Abstract: A reinvestigation of the mechanism of action of methylmercaptoimidazole, propylthiouracil, and thiouracil on thyroid peroxidase (TPO) was undertaken. A preliminary incubation of TPO and H2O2 with methylmercaptoimidazole, propylthiouracil, or thiouracil was carried out in the absence of oxidizable substrates (i.e. I- or guaiacol). This incubation resulted in irreversible inactivation of TPO. The extent of inactivation could be determined after removal of the drug by gel filtration or by dilution into the assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(52 citation statements)
references
References 25 publications
2
50
0
Order By: Relevance
“…Taurog and Dorris, on the other hand, suggested that the inhibition of iodination by compounds such as PTU involves a competition reaction between the drugs and tyrosine residues of thyroglobulin (Tg) for oxidized iodine. 14,16 In the present study, we have carried out the enzyme inhibition experiments with lactoperoxidase (LPO, figure 6) since it is readily available in purified form. 17 Furthermore, LPO has been shown to behave similarly to TPO with respect to iodination of thyroglobulin, the natural substrate, and other iodide acceptors.…”
Section: Inhibition Of Lactoperoxidase-catalysed Oxidationmentioning
confidence: 99%
“…Taurog and Dorris, on the other hand, suggested that the inhibition of iodination by compounds such as PTU involves a competition reaction between the drugs and tyrosine residues of thyroglobulin (Tg) for oxidized iodine. 14,16 In the present study, we have carried out the enzyme inhibition experiments with lactoperoxidase (LPO, figure 6) since it is readily available in purified form. 17 Furthermore, LPO has been shown to behave similarly to TPO with respect to iodination of thyroglobulin, the natural substrate, and other iodide acceptors.…”
Section: Inhibition Of Lactoperoxidase-catalysed Oxidationmentioning
confidence: 99%
“…Therefore, KI has been generally prescribed in limited situations such as preparation for thyroidectomy, treatment after radioactive iodine therapy for GD and correction of thyroid function of patients suffering from adverse effects of ATDs [6,7,13,14]. In addition, iodine administration in combination with ATDs has been reported to reduce the efficacy of ATDs in vitro [15][16][17]. There are also some reports that the combination of ATDs with iodine was not effective and KI monotherapy of GD impaired the efficacy of subsequent ATDs therapy [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the 2 drugs inhibit thyroid peroxidase (TPO)-catalyzed thyroid hormone formation (4); thus, the 2 drugs are mistakenly labeled as a TPO inhibitors by many clinicians. The antithyroid mechanisms of the 2 drugs have been described in the iodination system of cellfree experiments (5)(6)(7) and in vivo experiments in rats (7)(8)(9). These studies revealed reversible and irreversible inhibition of TPO-mediated reaction, as summarized by Taurog (10).…”
Section: Introductionmentioning
confidence: 99%